2008
DOI: 10.1309/ewygwfrrm8798u5p
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of False-Positive Histology According to the Reason for Colposcopy Referral in Cervical Cancer Screening

Abstract: All cervical intraepithelial neoplasia (CIN) diagnoses identified during the New Technologies for Cervical Cancer trial (ISRCTN81678807) were blindly reviewed by 2 pathologists. Original diagnoses based on colposcopy-guided biopsies were compared with those made by the reviewers who had access to all clinical histologic samples (including postsurgical). Cases downgraded from CIN 2+ by the reviewers were considered indicative of unnecessary treatments. The analyses are presented according to the molecular (high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 16 publications
2
24
0
2
Order By: Relevance
“…Overall, the loss in clinical sensitivity that resulted by missing the HPV types not targeted by HC2 would be small, in line with previous reports (15) suggesting that efforts to increase the number of targeted HPV types (i.e., HPV-53, HPV-66, and others) in HPV screening tests would not significantly improve clinical sensitivity. In addition, the probability of progression of these CINs is unknown, and histological false positives cannot be excluded (31,33). Conversely, improvements in analytical specificity would have a nonnegligible impact in reducing unneeded triage and/or colposcopy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the loss in clinical sensitivity that resulted by missing the HPV types not targeted by HC2 would be small, in line with previous reports (15) suggesting that efforts to increase the number of targeted HPV types (i.e., HPV-53, HPV-66, and others) in HPV screening tests would not significantly improve clinical sensitivity. In addition, the probability of progression of these CINs is unknown, and histological false positives cannot be excluded (31,33). Conversely, improvements in analytical specificity would have a nonnegligible impact in reducing unneeded triage and/or colposcopy.…”
Section: Discussionmentioning
confidence: 99%
“…All colposcopically suspected areas were biopsied. Biopsy samples of women with a CIN diagnosis were reviewed blindly to test results (31).…”
Section: Methodsmentioning
confidence: 99%
“…The same exercise was repeated at the time of the second screening round. The results of such reviews were previously reported 14, 16, 17, 22, 23. Adenocarcinoma in situ was considered with CIN3.…”
Section: Methodsmentioning
confidence: 99%
“…However, the grading characteristics can be quite subjective and pre-malignancy may not be visually perceptible at all. The sensitivity and specificity of colposcopy guided biopsy has been shown to be 75-90% and 97-99% respectively [12], but the subjective interpretation of histologic classification is the main issue leading to poor inter-observer agreement [13 -15].…”
Section: Histopathologymentioning
confidence: 99%